2009
DOI: 10.1007/s12105-009-0123-4
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the Head and Neck: An Overview

Abstract: This paper provides a review of the more common tumors to metastasize to 12 anatomic subsites of the head and neck, exclusive of cervical lymph nodes. Emphasis is placed on clinical rather than subclinical metastases discovered at autopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 57 publications
3
66
0
4
Order By: Relevance
“…Similarly, van der Waal et al [2] found that the most common primary sites for oral metastatic disease were lung and breasts. It has been postulated that metastatic lesions involve more commonly the jaws (65-75%) than the oral soft tissues (25-35%) [11]. Similarly, in our series, 72% of the cases spread to the bones.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, van der Waal et al [2] found that the most common primary sites for oral metastatic disease were lung and breasts. It has been postulated that metastatic lesions involve more commonly the jaws (65-75%) than the oral soft tissues (25-35%) [11]. Similarly, in our series, 72% of the cases spread to the bones.…”
Section: Discussionsupporting
confidence: 72%
“…Further, the vascular spaces in hematopoietic tissue are sinusoidal, allegedly allowing more easily penetration by tumor cells. In 5% of the cases, both the maxilla and mandible are affected [11], such as in one patient of our series.…”
Section: Discussionmentioning
confidence: 46%
“…Finally, one must consider metastasis from another primary site, although this is rare [22,23]. The most common tumors are melanoma and renal cell carcinoma, although rarely lung carcinomas can metastasize to the larynx (9% of all metastases to the larynx), so it is possible to tender metastatic pulmonary LCNEC as a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Barnes (2005) mentioned that this new wave of corporate philanthropy has its own ideological foundations that date to 2002 (Wilkinson 1991).The subject of strategic philanthropy therefore become very paramount especially in the post recession era in the united states where corporations were constantly reporting losses in the financial statements and many engaged in massive laid off and eventually closed down their different offices. Though the intention of this research is to lay the broad foundation for the problem that leads to the study or place this study in the context of the scholarly literature while reaching out to specific audience (Creswell,1994).…”
Section: Research Backgrounds and Motivesmentioning
confidence: 99%